Future time perspective and general self-efficacy mediate the association between awareness of age-related losses and depressive symptoms - Dutt, Anne J.; Wahl, Hans-Werner (European journal of ageing, 2019)
Perceiving one’s own aging process as associated with many losses is linked to an increase in depressive symptoms over 2.5 years. We investigated whether this pattern of associations also applies for a 4.5-year interval. No study has yet investigated the pathways underlying the association between perceived age-related losses and depressive symptoms. We examined the mediating role of future time perspective (FTP) and general self-efficacy (GSE) in this association. Analyses were based on a sample of 40-to-98-year-old adults (Time 1: 2012, N = 423) that was assessed at two additional points covering 4.5 years (Time 2: 2015, N = 356; Time 3: 2017, N = 299). Perceived age-related losses were operationalized via the loss dimension of the Awareness of Age-Related Change instrument; FTP, GSE, and depressive symptoms were assessed via established questionnaires. Data were analyzed by means of a cross-lagged panel model and longitudinal mediation model realized as a structural equation model. In line with prior findings, perceived age-related losses were associated with an increase in depressive symptoms over 4.5 years. A higher amount of perceived age-related losses dampened FTP and GSE 2.5 years later, which in turn increased the level of depressive symptoms a further 2 years later, controlling for age, sex, education, physical health, and neuroticism, and taking into account the stabilities and time-synchronous correlations of the study variables. Effects were comparable across middle-aged and older individuals. FTP and GSE are important resources for understanding how perceived age-related losses translate into depressive symptoms.